Ang lola kong babaylan an illustrated children's storybook series on the history and culture of the Babaylan - Amante, Kristienne Mae M.
The babaylan, or the Filipino traditional oralist-healers, have held one of the most important roles in early Filipino society. They sat among the datus and the pandays, and was responsible for some of the most major roles in early Filipino life, namely: Healing, leading religious rites, keeping tradition and culture of the people, and advising people, be it regarding farming, or mental health. These babaylan were among the first people to fight against colonization, thus, were also among the first to be persecuted. After a long history of manipulation, desecration, and persecution, the babaylan have receded into the background of Philippine history. In today's society, the babaylan have turned into a thing of the past. The tradition and culture they upheld and kept for centuries have been destroyed or forgotten. Despite wide awareness of their existence, the years of erasure and manipulation by the Spanish colonizers led to misinterpretation that carried on for years into the future. Students themselves do not know enough about the babaylan. Misinformation from adults passed on from generation to generation, mixed with the lack of educational materials and designated time and appreciation in the curriculum contribute to this lack of knowledge. Nowadays, in a recent technology boom, there are more than one ways to spread information. It is a wonderful thing to be able to utilize this to communicate, and for this purpose, to retrieve the image and good name of the babaylan from the negative perception of students and turn it into a positive and respectful name once more, and to provide a fun way for the children to learn new things based on the media they often touch up on and prefer. The children surveyed seem to know the basic meaning of the babaylan, being traditional healers, however they also have the negative perception of them being witches, terrible beings, and aswangs. Despite this, the children are enthusiastic to learn more about what the babaylan truly are. This study was conducted to supple information to people, to help them gain access to the data about the babaylan that they normally wouldn't have access to, in an entertaining way to make the data easier to digest for the children. Children were targeted for this informational campaign, because this is a topic they would be familiar with, based on the school's history curriculum. By targeting them while the information is still fresh, and supplying them with more information about this, it would help combat misinformation and keep them entertained enough to keep the information for long. Informing the children about the history and culture of the babaylan is important because it would also mean informing them of the history and culture of the Philippines. The babaylan are integral parts of the early Philippines communities, and they held positions of great importance, therefore Philippine history and culture would not be complete if the babaylan were taken out of the narrative. Surveys and interviews were conducted to ensure the correctness of the data gathered, and to find out what the children would want in their media. It was found out that the children love illustration and reading. They like adventure, fantasy, and roleplay: thus the product was a book series packed with the information needed to understand the history and culture of the babaylan, and designed to cater to their desire for illustration and reading. By mixing historical facts and fantasy in a narrative, it creates a way for children to want to read it and absorb information at the same time.